Design of Massive Actuators For 3D Robot Manipulators - Felix Pasila (IAES Indonesia Section, 2015)
In this paper, a novel parallel manipulator with discrete control system is developed. An efficient method such as Inverse Static Analysis (ISA) is employed to determine the state of each actuator on parallel manipulator when the position or force of manipulator is already known. The designing a parallel manipulator with 16 actuators which are controlled discretely is a must because the mechanism will use artificial methods in dealing with the ISA problem. In this approach, mathematical model is not required. The research method used simulation software and hardware testing with the case of parallel manipulator with 16 actuators. Simulations with typical desired force inputs are presented and a good performance of the mechanism is obtained. The results showed that the parallel manipulator has the Root Mean Squared Error (RMSE) has less than 3% and can be used for artificial intelligence implementation.